Building a Culture of Islamic Coordination in the Digital Era to Improve Organizational Performance - Ninda Meiliani Lubis; Nadra Rizki Miharsa; Ahmad Nurdin Siregar (Penerbit Merdeka Kreasi, 2024)
Digital transformation has fundamentally changed organizational dynamics, demanding an adaptive, efficient, and valuable coordination model. In the context of Islamic organizations, the need for coordination is not only technical, but also spiritual. This research aims to examine how the culture of Islamic coordination is built and implemented in organizations in the digital era and how it affects the improvement of organizational performance. Using a descriptive qualitative approach, data was collected through in-depth interviews, observations, and documentation studies at a number of Islamic-based institutions that have integrated Islamic values in digitization practices. The results of the study show that the integration of Islamic values such as ta'awun (cooperation), amanah (trust), shiddiq (honesty), and ihsan (excellence) in the organization's digital system is able to form a harmonious, collaborative, and productive work culture. The use of technology such as cloud systems, digital communication platforms, and work management applications strengthens the coordination process while maintaining accountability according to the principle of hishbah. The Islamic culture of coordination also increases loyalty and job satisfaction, strengthens participatory leadership, and forms a balanced work system between the mundane and ukhrawi. This research confirms that building a culture of Islamic coordination in the digital era not only supports organizational effectiveness, but is also a superior strategy to maintain integrity, strengthen identity, and increase competitiveness. Thus, this approach is worthy of being used as a model for Islamic organizations in facing global challenges based on values and technology.